The emotional impact of verbal irony: eye-tracking evidence for a two-stage process - Filik, Ruth; Brightman, Emily; Gathercole, Chloe; Leuthold, Hartmut (Elsevier, 2017)
In this paper we investigate the socio-emotional functions of verbal irony. Specifically, we use eye-tracking while reading to assess moment-to-moment processing of a character’s emotional response to ironic versus literal criticism. In Experiment 1, participants read stories describing a character being upset following criticism from another character. Results showed that participants initially more easily integrated a hurt response following ironic criticism; but later found it easier to integrate a hurt response following literal criticism. In Experiment 2, characters were instead described as having an amused response, which participants ultimately integrated more easily following ironic criticism. From this we propose a two-stage process of emotional responding to irony: Whilst readers may initially expect a character to be more hurt by ironic than literal criticism, they ultimately rationalise ironic criticism as being less hurtful, and more amusing.